Kinetic studies of Composting Using Empty Fruit Bunch (EFB) / \c Ahmad Salahuddin Azhar - Ahmad Salahudddin Azhar (School of Bioprocess Engineering, University Malaysia Perlis, 2012)
Empty fruit bunches (EFB)is a by-product of palm oil mills. As the word's leading exporter of palm oil products, Malaysia generates a high number of EFB per year. Conventional treatment for EFB requires a large area and the burning of EFB releases a very amount of carbon monoxide. To create a concept of zero waste from palm oil mills, biocomposing of EFB is better for its low cost and likely to generate income. In this study, The process conditions that affect the biocomposting process are determined and the process kinetic in biocomposting of EFB is examined. This study is examines the process kinetics by experimenting with laboratory-scale equipment under controlled biocomposting conditions to show theinterdependencesbetween biological and physical factors during the biocomposting of EFB>